NBN 657del5 heterozygous mutations and colorectal cancer risk in the Czech Republic - Pardini, Barbara; Naccarati, Alessio; Polakova, Veronika; Smerhovsky, Zdenek; Hlavata, Ivona; Soucek, Pavel; Novotny, Jan; Vodickova, Ludmila; Tomanova, Vera; Landi, Stefano; Vodicka, Pavel (Mutation research, 2009)
The most frequent Nijmegen breakage syndrome (NBS)-causing mutation is a 5-base pair deletion in gene coding for nibrin (NBN 657del5), which results in a non-fully functional protein product and is particularly frequent in Central and Eastern Europe. Recent studies have investigated whether NBN 657del5 carriage may predispose to an increased risk of different types of cancer. The Czech Republic has one of the highest incidences of colorectal cancer in the world as well as high incidence of NBS. To assess whether NBN 657del5 associates with an increased risk of sporadic colorectal cancer, we have screened 771 colorectal cancer patients, 614 controls with negative colonoscopy and 818 healthy blood donors from the Czech Republic. There were no significant differences between the frequencies of heterozygous carriers among the three groups. The present results do not provide any evidence that the exceeding risk of CRC in this population is attributable to the high frequency of heterozygous carriage of the NBN 657del5.
Keywords: Humans; lidé středního věku; Female; mutace; Aged; dospělí; jaderné proteiny; senioři; lidé; Genotype; Cell Cycle Proteins; Sequence Deletion; Adult; ženské pohlaví; sekvenční delece; kolorektální nádory; Male; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; Nuclear Proteins; Czech Republic; proteiny buněčného cyklu; Aged, 80 and over; Heterozygote; senioři nad 80 let; genotyp; heterozygot; Mutation; Česká republika; mužské pohlaví; Colorectal Neoplasms